Changes in self‐reported symptoms of depression and physical well‐being in healthy individuals following a Taiji beginner course – Results of a randomized controlled trial. Issue 4 (4th March 2016) - Schitter, Agnes Maria; Nedeljkovic, Marko; Ausfeld‐Hafter, Brigitte; Fleckenstein, Johannes
Abstract: Background: Taiji is a mind–body practice being increasingly investigated for its therapeutic benefits in a broad range of mental and physical conditions. The aim of this study was to investigate the potential preventive effects of Taiji practice in healthy individuals with regard to their depressive symptomatology and physical well‐being. Methods: Seventy healthy Taiji novices were randomly assigned to a Taiji intervention group, that is, Taiji beginner course (Yang‐Style Taiji, 2 h per week, 12 weeks) or a control group comprised of the waiting list for the course. Self‐reported symptoms of depression (CES‐D) and physical well‐being (FEW‐16) were assessed at baseline, at the end of the intervention, as well as 2 months later. Results: The included participants had a mean age of 35.5 years. Physical well‐being in the Taiji group significantly increased when comparing baseline to follow‐up (FEW‐16 sum score T (27) = 3.94, P =  0.001, 95% CI 0.17 to 0.55). Pearson's correlation coefficients displayed a strong negative relationship between self‐reported symptoms of depression and physical well‐being ( P 's < 0.001, r 's ≥ −0.54). Conclusion: In this randomized controlled trial, we found significant evidence that a Taiji beginner course of 3 months duration elicits positive effects with respect to physical well‐being in healthy individuals, with improvements pronouncing over time. Physical well‐being was shown to have a strong relationship with depressive symptoms. Based on these results, the consideration of Taiji as one therapeutic option in the development of multimodal approaches in the prevention of depression seems justifiable. Abstract : Seventy healthy Taiji novices (mean age 35.5 years) were randomly assigned to a Taiji intervention group, that is, Taiji beginner course (Yang‐Style Taiji, 2 h per week, 12 weeks) or a control group comprised of the waiting list for the course. Self‐reported symptoms of depression (CES‐D) and physical well‐being (FEW‐16) were assessed at baseline, at the end of the intervention, as well as 2 months later. We found significant evidence that a Taiji beginner course of 3 months duration elicits positive effects with respect to physical well‐being in healthy individuals, with improvements pronouncing over time.